Voiding cinema: subjectivity beside itself, or unbecoming cinema in Enter the void - Brown, William; Fleming, David H. (Edinburgh University Press, 2015)
This essay examines Gaspar Noë's film, Enter the Void (2009), in light of the work of both Gilles Deleuze and Alain Badiou. Arguing that the film shows to viewers the 'void' that separates subjects from objects, the essay also considers Noë's film in the light of drug literature and the altered states induced by cinema and describe by Anna Powell. Finally, the essay proposes that Enter the Void is a work of 'unbecoming' cinema, which in turn points to expansion of cinematic form through the use of digital technologies.